Testing the predictive power of term spread in the Euro area - Rimal, Sachindra (2021)
This thesis tests the predictive power of term spread in predicting the Euro area's real economic activities. The objectives of this study are to test the predictive power of term spread in the negative interest rate period in the Euro area, to examine the joint predictive power of term spread and EPU, and to reveal the Granger causality of the variables.